Differential targeting of cPKC and nPKC decodes and regulates Ca2+ and lipid signalling. (17th November 2014) - Hui, Xin; Kaestner, Lars; Lipp, Peter
Abstract : Protein kinases C (PKCs) are ubiquitously expressed and play critical roles in a plethora of physiological and pathophysiological processes. Owing to PKCs' highly conserved phosphorylation consensus sequence, it has been difficult to distinguish the role of individual PKC isoforms. Recently, the identification of novel membrane targeting via subcellularly targeted diacylglycerol production found for novel PKCs (nPKCs), together with a characterization of their putative functions, has shed new light on the specific roles of individual PKCs in cellular processes.